Сутність та основні моделі децентралізації управління вищою освітою у зарубіжних країнах та в Україні - Пашков, Віктор (Studies in Comparative Education, 2014)
У статті розглянуто проблеми та моделі децентралізації керування вищою освітою. Автором розкрито сутність процесу та політики децентралізації, основні причини її запровадження та позитивні ефекти від її реалізації. Обґрунтовано, що децентралізація є формою лібералізації управління вищою школою з боку держави, що має на меті підвищення ефективності діяльності та суспільної відповідальності ВНЗ. На прикладі зарубіжних країн проаналізовано можливі ефекти від використання різних моделей здійснення політики децентралізації, а також зроблено висновки щодо України. В статье рассмотрены основные модели децентрализации управления высшим образованием. Автор рассматривает суть процесса децентрализации, главные причины ее внедрения и позитивные моменты ее реализации. Децентрализация представлена как форма либерализации управления высшим образованием со стороны государства, нацеленная на повышение эффективности функционирования и общественной ответственности вуза. На примерах зарубежных стран проанализированы возможные эффекты различных моделей внедрения политики децентрализации. Кроме того, сделаны выводы относительно возможного внедрения зарубіжного опыта в Украине. The article studies problems and models of decentralization of governance in the higher education. On example of different countries author analyses potential effects from use of different models of decentralization, also author concludes about situation in Ukraine. The author proves that the decentralization of higher education, which actively is pursued by governments of leading countries in the last quarter of the XX century, aimed at improving the efficiency of a use of public funds and approaching the performance of universities to the needs of the national economy and local communities. On the basis of generalization of world experience decentralization author identifies three most common models of implementation of decentralization – deconcentration; delegation of authority to academic leadership and elite; delegation of authority directly to universities. Deconcentration means delegation of authority and financial responsibility for development of higher education to regional governments. The role of central government limits by coordination, support of priority scientific projects and investments in educational infrastructure. Deconcentration promotes of harmonization of higher education and local labor market. This model of decentralization is typical for China, India, Germany, Spain and Switzerland. Delegation of authority to academic leadership and elite provides transfer political, financial responsibility from state to representative bodies of academic community, which consists of academic leadership. Such transfer facilitates strengthening of principles of self-regulation in system of higher education. This model of decentralization is typical for the UK, New Zealand, partially for India, Germany. Delegation of authority directly to universities means their transformation on independent academic corporations, that are wholly responsible for their actions, quality of educational services, form own development strategy. Such decentralized and independent universities are interested in effective use of financial resources, which they receive from the environment. This model is presented by the USA and Canada.